2005
DOI: 10.17221/3553-pse
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mineral treatment and the amendments by organic and organomineral fertilisers on the crop yield, plant nutrient status and soil properties

Abstract: The studies were carried out as a pot experiment comprised of mineral treatments with farmyard manure, slurry and liquid organomineral fertiliser (Damishum) and finally the unfertilised control. Mineral fertilisation and liquid organomineral fertiliser be�er affected the crop yield in comparison with organic treatments in the first year of the experiment, whereas in the subsequent two years with a consecutive affect of organic fertilisers. According to the expectations the biggest nitrogen concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
0
11
1
Order By: Relevance
“…A recent study demonstrated that there was a statistically significant correlation (P ≤ 0.01) between the grain yields and organic C content of soil after application of organic amendments to soil (Mikanová et al 2012). The combined application of farm manure and mineral fertilizer could induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek andFilipek-Mazur 2005, Verma et al 2012). As a result of an increase in nutrient level of soil, a significant effect (P ≤ 0.05) on yield per hectare was determined (Milosevic and Milosevic 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that there was a statistically significant correlation (P ≤ 0.01) between the grain yields and organic C content of soil after application of organic amendments to soil (Mikanová et al 2012). The combined application of farm manure and mineral fertilizer could induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek andFilipek-Mazur 2005, Verma et al 2012). As a result of an increase in nutrient level of soil, a significant effect (P ≤ 0.05) on yield per hectare was determined (Milosevic and Milosevic 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The farm manure and HA caused an increase in the organic carbon content in the soil (Gondek and Filipek-Mazur 2005) and positively affected the root growth of rice crop. The incorporation of organic manure into soil can bring beneficial effects on crop root growth by improving physical and chemical environments of rhizosphere (Sidiras et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are also in agreement with Ali and Abbas (2003) and Muhammad and Khattak (2011), that OM increases the amount of soluble Ca 2+ for soil reclamation. Application of a combination of OM and mineral fertilizer may induce an increase in the humus content, nitrogen, and available phosphorus and potassium levels (Gondek and Filipek-Mazur, 2005). Moreover, a previous study showed that cv.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, Kumar et al (2007) reported that the distillery effluent based pressmud compost (DEPC), farmyard manure (FYM), combinations of DEPC+FYM and inorganic fertilizer significantly increased the seed yield and quality content of Indian mustard. Gondek and Filipek (2005) compared the effects of mineral treatments and the amendments by organic and organomineral fertilizers on rape plants. They stated that mineral fertilizer and liquid organomineral fertilizer application better affected crop yield in comparison with organic treatments in the first year of the experiment, whereas in the subsequent two years a consecutive effect of organic fertilizers was observed.…”
Section: Introductionmentioning
confidence: 99%